Cardiovascular screening of athletes - Beckerman, J.; Wang, P.; Hlatky, M. (Clinical Journal of Sport Medicine, 2004)
Cardiovascular screening of athletes is a challenging aspect of the preparticipation evaluation. While sudden cardiac death in young athletes is uncommon, preparticipation screening may identify some predisposing conditions that place individuals at increased risk. The most common pre-existing cardiac abnormalities in athletes causing sudden death in the United States are hypertrophic cardiomyopathy, congenital coronary anomalies, and Marfan syndrome. Preparticipation cardiovascular screening should pursue any history of cardiac symptoms or family history of premature cardiac disease, as well as abnormal cardiovascular physical findings. Positive findings should be investigated; an electrocardiogram, echocardiogram, or consultation with a specialist should be considered. Recommendations are then available to guide athletic participation according to the cardiovascular diagnosis.